Cell salvage and donor blood transfusion during Caesarean section: a pragmatic multicentre randomised controlled trial (SALVO) - Khan, Khalid S.; Moore, Philip A.S.; Wilson, Matthew J.; Hooper, Richard; Allard, Shubha; Wrench, Ian; Beresford, Lee; Roberts, Tracy E.; McLoughlin, Carol; Geoghegan, James; Daniels, Jane P.; Catling, Sue; et al. (Public Library of Science, 2017)
Background: Excessive haemorrhage at caesarean section requires donor (allogeneic) blood transfusion. Cell 34 salvage may reduce this requirement. Methods and findings: We conducted a pragmatic randomised controlled trial (26 obstetric units; June 2013 through April 2016) of routine cell salvage use (intervention) vs. current standard of care without routine salvage use (control) in caesarean section among women at risk of haemorrhage. Randomisation was stratified, using random permuted blocks of variable sizes. In an intention-to-treat analysis, we used multivariable models, adjusting for stratification variables and prognostic factors identified a priori, to compare rates of donor blood transfusion (primary outcome) and fetomaternal haemorrhage ≥2ml in RhD-negative women with RhD-positive baby (a secondary outcome) between groups. Among 3028 women randomised (2990 analysed), 95.6% of 1498 assigned to intervention had cell salvage deployed (50.8% had salvaged blood returned; mean 259.9 ml) vs. 3.9% of 1492 assigned to control. Donor blood transfusion rates were 3.5% in the control group vs. 2.5% in intervention (adjusted odds ratio [OR] 0.65, 95% confidence interval [CI] 0.42 to 1.01, p=0.056; adjusted risk difference -1.03, 95% CI -2.13 to 0.06; number needed to treat [NNT] 97, at the lower limit of 95% confidence NNT was 47 and at the upper limit the number needed to harm was 1,667). In a planned subgroup analysis, the transfusion rate was 4.6% in women assigned to control vs. 3.0% in the intervention group among emergency caesareans (adjusted OR 0.58, 95% CI 0.34 to 0.99), whereas it was 2.2% vs. 1.8% among elective caesareans (adjusted OR 0.83, 95% CI 0.38 to 1.83) (interaction p=0.46). No case of amniotic fluid embolism was observed. Fetomaternal haemorrhage was higher with intervention (10.5% in control vs. 25.6% in intervention, adjusted OR 5.63, 95% CI 1.43 to 22.14, p=0.013). We are unable to comment on long-term antibody sensitisation effects. Conclusions: The overall reduction observed in donor blood transfusion associated with the routine use of cell salvage during caesarean section was not statistically significant.